2017
DOI: 10.1161/jaha.117.006202
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Coronary Revascularization on the Prognostic Value of Stress Myocardial Contrast Wall Motion and Perfusion Imaging

Abstract: BackgroundThe assessment of myocardial perfusion (MP) and wall motion (WM) using contrast dipyridamole echocardiography (cSE‐WMP) improves the sensitivity to detect coronary artery disease and the stratification of cardiac events, but its long‐term value for fatal and nonfatal ischemic cardiac events, also with respect to patients undergoing revascularization or not, remains to be determined.Methods and ResultsOne‐thousand three‐hundred and twenty‐nine patients with suspect or known CAD who underwent cSE‐WMP w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 32 publications
(27 citation statements)
references
References 31 publications
0
25
0
2
Order By: Relevance
“…6 Studies using other stress modalities reported similar findings of an association of more ischemia and higher risk of death or MI. 11,[13][14][15][16][17][18] However, even in propensity-matched cohorts there is residual confounding, and a clinical trial was needed to verify this finding. Moreover, these patients did not receive OMT by contemporary standards, while in ISCHEMIA, the median baseline lowdensity lipoprotein cholesterol level was 83 mg/dL, with high rates of use of aspirin and potent statins, and this was prior to intensification of medical therapy when needed to achieve risk factor goals.…”
Section: Discussionmentioning
confidence: 99%
“…6 Studies using other stress modalities reported similar findings of an association of more ischemia and higher risk of death or MI. 11,[13][14][15][16][17][18] However, even in propensity-matched cohorts there is residual confounding, and a clinical trial was needed to verify this finding. Moreover, these patients did not receive OMT by contemporary standards, while in ISCHEMIA, the median baseline lowdensity lipoprotein cholesterol level was 83 mg/dL, with high rates of use of aspirin and potent statins, and this was prior to intensification of medical therapy when needed to achieve risk factor goals.…”
Section: Discussionmentioning
confidence: 99%
“…Functional evidence of ischemia remains the major criterion for prognostically relevant CAD [ 48 50 ]. In 2011, a study by Krittayaphong et al assessed the prognostic value of combined myocardial perfusion CMR and LGE, thus identifying myocardial ischemia as the strongest predictor for hard cardiac events and major adverse cardiac events (MACE) among patients with known or suspected CAD [ 51 ].…”
Section: Prognostic Role Of Stress Cmrmentioning
confidence: 99%
“…Несмотря на наличие исследований, подтверждающих прогностическую роль изолированного нарушения перфузии миокарда [15,16], остается открытым вопрос о необходимости реваскуляризации таких больных. Существует нерандомизированное ретроспективное исследование, показавшее, что проведение чрескожного коронарного вмешательства (ЧКВ) у таких пациентов ассоциировано с более высоким риском смерти и тяжелых кардиальных событий, чем у пациентов, находившихся на медикаментозной терапии [17]. Вопрос этот не решен.…”
Section: миокардиальная контрастная стресс-эхокардиографияunclassified